Pengaruh Pengetahuan Kewirausahaan dan Keterampilan Wirausaha Terhadap Keberhasilan Usaha (Studi Kasus UMKM Pusat Pasar Kota Medan) - Silaban, Doni Enriko; Aisyah, Nur; Lubis, Adelina (Mahesa Research Center, 2025)
The purpose of this research is to determine the influence of entrepreneurial knowledge on business success, to determine the influence of business capital on business success, and to determine the influence of entrepreneurial knowledge and business capital on business success (case study of MSMEs at the Medan City Market Center). The population in this study was 1,821 business actors in the Medan City Market Center. The sample in the research was 95 business actors taken using the Slovin formula. The data collection technique used in this research was carried out by distributing questionnaires. The analysis techniques used in this research are multiple linear regression, partial test (t test), simultaneous significance test (F test), and coefficient of determination. The research results show that entrepreneurial knowledge has a positive and significant effect on business success, business capital has a positive and significant effect on business success, and entrepreneurial knowledge and business capital have a significant and simultaneous effect on the success of MSME businesses in the Medan City Market Center.